Evaluation of the Changes in Mental Health State at the Beginning of COVID-19 in Hospital Personnel (Bangladesh Journal of Medicine, 2021)
Objective: In the present study, it was aimed to determine the changes in the mental states of hospital personnel at the beginning of COVID-19 pandemic, and the factors affecting these changes.Methods: The research sample consisted of 299 hospital personnel in Turkey, who could be reached with the online method. The data were collected using the “Information Form”, which was prepared in line with the literature and the pandemic process, “The Impact of Event Scale (IES)” and the “Depression-Anxiety-Stress Scale (DAS-21)”.Results: It was found that the sociodemographic characteristics, medical history, and the characteristics related to COVID-19 were effective on the participants in terms of their mental states and the way they perceived traumatic experiences. According to the multiple linear regression analyses, it was found that hyper arousal and reexperiencing predicted stress, anxiety, and depression with a rate of 58.5%, 59.0% and 60.6%, respectively.Conclusion: At the beginning of the pandemic, it was observed that the responses of frontline hospital employees to traumatic experiences affected their mental states. Psychiatric nurses should take an active role in the development and implementation of psychosocial support programs for hospital personnel.Bangladesh J Medicine July 2022; 33(1) : 19-26